2018
DOI: 10.1021/acs.jmedchem.7b01340
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Synthesis of Amino Acid-Derived Thiazole Peptidomimetic Analogues to Understand the Enigmatic Drug/Substrate-Binding Site of P-Glycoprotein

Abstract: A novel set of 64 analogues based on our lead compound 1 was designed and synthesized with an initial objective of understanding the structural requirements of ligands binding to a highly perplexing substrate-binding site of P-glycoprotein (P-gp) and their effect on modulating the ATPase function of the efflux pump. Compound 1, a stimulator of P-gp ATPase activity, was transformed to ATPase inhibitory compounds 39, 53, and 109. The ATPase inhibition by these compounds was predominantly contributed by the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…012 software. Ligand preparations for VKNG-2 were done using Lig-prep [ 76 ]. A homology model of human ABBC1 was imported from the protein data bank.…”
Section: Methodsmentioning
confidence: 99%
“…012 software. Ligand preparations for VKNG-2 were done using Lig-prep [ 76 ]. A homology model of human ABBC1 was imported from the protein data bank.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo study [67] showed TTT-28 enhanced intratumoral concentration of placitaxel, inhibiting the growth of ABCB1 overexpressing tumors. Additional extensive derivatizations of TTT-28 in terminal groups and central thiazole building block side chain helped to understand the drug/substrate interactions with P-gp [68]. Modifications on these sites led to divergent effects in ATPase efflux pump, from initial stimulation in TTT-28 to inhibition.…”
Section: Linear Peptidesmentioning
confidence: 99%
“…The structural basis for the distinction between these nucleosides in their interaction with P-gp is the presence of a 2-chlorine atom in compound 23, which is hydrogen in 22. These results could be due to the flexible nature of P-gp, which enables the protein to recognize various sizes and types of chemical structures (Patel et al, 2018); however, it should be noted that the affinity of both nucleosides at the target A 3 adenosine receptor is ∼1 nM, and selectivity for the clinically relevant pathway is unchanged.…”
Section: Resultsmentioning
confidence: 99%